Modelling of nitrogen leaching from watersheds with large drained peat areas. (November 2018) - Vassiljev, Anatoli; Kaur, Katrin; Annus, Ivar
Highlights: The SOIL and MACRO models with different versions of SOILN initially developed for small field-scales were used to simulate the water flow and nitrate N concentrations at the watershed scale. Water quantity and quality of two watersheds in Estonia with large percentage of drained peat soils were modelled. The analysis showed that over the 11 year study period, the average nitrogen loads from drained peat soils were 1.5 times higher than those from clay loam (arable lands). Abstract: The SOIL and MACRO models with different versions of SOILN initially developed for small field-scales were used to simulate the water flow and nitrate N concentrations in two watersheds in Estonia that contain large areas of peat soils. Monitoring data show that nitrogen concentrations tend to increase in some rivers even where the human activity is very low. This may be connected to soil self-degradation processes taking place in drained peat soils where it is difficult to use most of the hydrological models. Results show that SOIL, MACRO and SOILN may be successfully applied at the watershed scale to model the water quantity and quality on watersheds with high content of peat soils. The analysis revealed that the nitrate nitrogen level trends depend considerably on the meteorological conditions.